Analisis Kegiatan Remedial untuk Siswa Kelas V-C yang Mengalami Kesulitan Penjumlahan dan Pengurangan Pecahan Campuran Di SDN Rangkah I Surabaya - Djayanti Wiulan Sari; Umik Hanik; Indah Setyowardhani; Bagus Rahmad Wijaya; Nova Estu Harsiwi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Students who experience difficulties in learning are the teacher's responsibility to overcome the problems faced by students. One of the actions that teachers can take to help students with learning difficulties is through providing remedial activities. The purpose of this research is to find out the steps, obstacles and solutions to the problems of class V-C teachers in implementing remedial activities for students who experience difficulty adding and subtracting mixed fractions at SDN Rangkah I Surabaya. This research uses a method with a descriptive qualitative approach. This research uses data collection techniques using observation, interviews and documentation techniques. The results of this research are 1). The teacher's steps in implementing remedial activities are that the teacher analyzes the results of the diagnosis of student difficulties by referring to student test scores that are below the KKTP score of 60. Next, by planning remedial activities, the teacher arranges the day, date, time, method, media and prepares the questions that will be created for the activity. remedial. After everything has been carefully planned for remedial activities, the next step is for the teacher to carry out remedial activities for four students who are experiencing difficulties. Next, after carrying out the remedial activities, the teacher assesses the results of the remedial work for each student who took part in the remedial activities. 2). The obstacles for teachers in implementing remedial activities are that they require quite a long time, the physical condition of students is not enthusiastic and the differences in the characteristics of students' comprehension abilities. 3). The teacher's solution to the obstacles in implementing remedial activities is that the teacher maximizes the time for remedial activities, the teacher always provides encouragement in every implementation of remedial activities and the teacher explains again to students who do not understand the explanation individually.